THE IMPACT OF THE PCE MC CORRECTION VALUE USING MODIFIED AVERAGE TIME HEADWAY METHOD TO ROAD PERFORMANCE (CASE STUDY: VETERAN STREET, MALANG CITY) - Primasari Cahya Wardhani; Ahmad Dzulfiqar Alfiansyah (Journal of Civil Engineering Science and Technology (CI-TECH), 2022)
Passenger Car Equivalent (PCE) is a conversion factor of various types of vehicles compared to passenger cars or other light vehicles concerning their impact on traffic behavior. The PCE value used in calculating the performance of urban roads refers to Manual Kapasitas Jalan Indonesia (MKJI 1997) as an Indonesian Highway Capacity Manual. There have been many changes in traffic behavior nowadays compared to in 1997. The calculation of the PCE MC value using the average time headway method does not match the actual conditions. Therefore, modifications are needed by calculating the vehicle dimension factors to obtain the PCE value. The result of the PCE MC calculation using the modified average time headway method shows 0.17. This value is smaller than the value of the PCE MC set by the MKJI 1997, which shows 0.25. Based on the analysis of traffic conditions for ten years, the DS value using the PCE MC according to the MKJI 1997 obtains DS>1. Meanwhile, the DS value calculated based on the corrected PCE MC has DS<1. The difference in the value of PCE MC has implications for road performance. As a result, it affects traffic maintenance management in the form of maintenance costs and decision-making.